Learning How to Innovate: Standard Chartered Bank's iLab@SMU Challenges Students to Bridge Technology and Business - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
"The future of banking is in Asia and the key driver is innovation," according to a statement from Standard Chartered Bank and the Singapore Management University, which together established an innovation centre -- the Standard Chartered iLab@SMU -- in early 2006. Students can work with iLab on projects where they are exposed to a corporate environment and issues relating to managing intellectual property. As an example, several students were recently given the challenge of investigating the viability of voice biometrics authentication technology at the bank. Knowledge@SMU interviewed both the students and bank executives for their views on how the process worked.